Innovation, Governance, and Sustainability of Waqf Institutions: The Mediating Role of Investment and Asset Risk - Tina Kartini; Sri Widyastuti; Darmansyah (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Sustainability has become a major challenge for waqf institutions, as faith-based nonprofit organizations are required to preserve assets perpetually while delivering long-term socio-economic benefits. Many waqf institutions, however, face constraints such as limited innovation, weak governance, and increasing investment and asset risks. This study aims to examine the influence of innovation and governance on the sustainability of waqf institutions, with investment risk and asset risk serving as mediating mechanisms within the framework of maqasid al-shariah. A qualitative multiple case study approach was employed, focusing on Muhammadiyah waqf management units in West Java, Indonesia. Data were collected through semi-structured in-depth interviews, observations, and document analysis, and were analyzed using thematic analysis with triangulation procedures to ensure credibility. Findings indicate that innovation enhances operational efficiency, financial resilience, and social impact, while governance strengthens transparency, accountability, and institutional trust. However, innovation also increases exposure to investment and asset risks, which must be managed through effective governance and risk management. The study concludes that sustainable waqf management is achieved through a balanced integration of innovation, governance, and risk management in accordance with maqasid al-shariah principles.